Effect of different gelators on the physicochemical properties and microstructure of coconut oleogels - Yang, Zihan; Cui, Jingtao; Yun, Yonghuan; Xu, Yongjiang; Tan, Chin Ping; Zhang, Weimin (John Wiley and Sons, 2024)
BACKGROUND The inherent properties of coconut oil (CO), including its elevated saturated fatty acid content and low melting point, make it suitable for application in plastic fat processing. The present study explores the physicochemical characteristics, micromorphology and oxidative stability of oleogels produced from CO using various gelators [ethylcellulose (EC), β-sitosterol/γ-oryzanol (PS) and glyceryl monostearate (MG)] to elucidate the formation mechanisms of coconut oleogels (EC-COO, PS-COO and MG-COO).